2018
DOI: 10.1001/jama.2018.12358
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in First Gabapentin and Pregabalin Prescriptions in Primary Care in the United Kingdom, 1993-2017

Abstract: Given the safety concerns of gabapentinoids and the lack of robust evidence supporting their efficacy in cases of nonneuropathic pain, 6 caution is necessary when prescribing gabapentinoids, especially among patients also prescribed opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 6 publications
4
113
2
Order By: Relevance
“…The use of GBP in Norway was shown to gradually increase from 2007 to 2015, 4,5 due to an increase in use in neuropathic pain. 27 27 …”
Section: Use Of Gbp In Norwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of GBP in Norway was shown to gradually increase from 2007 to 2015, 4,5 due to an increase in use in neuropathic pain. 27 27 …”
Section: Use Of Gbp In Norwaymentioning
confidence: 99%
“…4 Increased use has also been demonstrated internationally, with a recent study from United Kingdom finding a large increase in the rate of patients newly treated with GBP from 2007 to 2017. 27…”
Section: Use Of Gbp In Norwaymentioning
confidence: 99%
“…Parkinson's disease (PD) is a common neurodegenerative disorder, and the major unmet needs of PD are the identification of reliable biomarkers and the development of successful disease-modifying treatments, 2 issues that are basically linked to a better comprehension of the disease pathogenesis. 1,2 Compelling evidence indicates that oxidative stress and neuroinflammation play central roles in the pathophysiology of PD. [3][4][5][6] These processes are critically modulated by the transcription factor nuclear factor erythroid-2-related factor 2 (Nrf2), a master regulator of cellular defence.…”
Section: Introductionmentioning
confidence: 99%
“…Gabapentinoids, such as gabapentin and pregabalin, are indicated in neuropathic pain and epilepsy. Recent US and European data have shown that their use tripled during the last decade, and there has been a high level of off‐label prescriptions and misuse . Although side effects, such as somnolence, dizziness, and ataxia, are usually mild, long‐term adverse effects are unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation